2015
DOI: 10.1017/s1355617715000855
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Associative Learning Effects in Patients with Prodromal Alzheimer’s Disease Using the Temporal Context Model

Abstract: Objective: The purpose of this study was to investigate associative learning effects in patients with prodromal Alzheimer's disease (prAD) by referring to the Temporal Context Model (TCM; Howard, Jing, Rao, Provyn, & Datey, 2009), in an attempt to enhance the understanding of their associative memory impairment. TCM explains fundamental effects described in classical free-recall tasks and cued-recall tasks involving overlapping word pairs (e.g., A-B, B-C), namely (1) the contiguity effect, which is the tendenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…Aβ (1–42) treatment to hippocampal rat slices have been known to affect long‐term plasticity (late LTP) and associativity such as synaptic tagging and capture (STC) (Jiang et al, ; Krishna et al, ; Lei et al, ; Ma et al, ; Quenon, de Xivry, Hanseeuw, & Ivanoiu, ; Sharma et al, ). Since the impaired synaptic plasticity was associated with the upregulation of miR‐134‐5p expression in rat hippocampal slices, we investigated if inhibition of miR‐134‐5p expression using miR‐134i could rescue late LTP in Aβ (1–42)‐treated hippocampal slices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aβ (1–42) treatment to hippocampal rat slices have been known to affect long‐term plasticity (late LTP) and associativity such as synaptic tagging and capture (STC) (Jiang et al, ; Krishna et al, ; Lei et al, ; Ma et al, ; Quenon, de Xivry, Hanseeuw, & Ivanoiu, ; Sharma et al, ). Since the impaired synaptic plasticity was associated with the upregulation of miR‐134‐5p expression in rat hippocampal slices, we investigated if inhibition of miR‐134‐5p expression using miR‐134i could rescue late LTP in Aβ (1–42)‐treated hippocampal slices.…”
Section: Resultsmentioning
confidence: 99%
“…Synaptic associativity such as synaptic tagging and capture (STC), a unique feature of healthy neurons, enables weak memory engram to transform to relatively stable memory engram and thus helps with the formation of long‐term memory (Frey & Morris, ; Redondo & Morris, ; Sajikumar & Frey, ). Various studies have reported the dysregulation of synaptic associativity in AD pathology (Bastin et al, ; Jiang et al, ; Quenon et al, ). It has been reported earlier that STC is highly impaired during aging and in Aβ‐induced AD conditions (Sharma et al, , ; Shetty & Sajikumar, ).…”
Section: Discussionmentioning
confidence: 99%
“…The conversion of short‐term plasticity to long‐term plasticity widely relies on associative properties of a neural network. One characteristic feature of progressive dementia and AD is the deficit in associative plasticity or memory (Bastin et al ., ; Jiang et al ., ; Quenon et al ., ). Our data provide the evidence that Aβ leads to deficits in synaptic tagging/capture (STC), which is considered as one of the major contributors of associative plasticity (Frey & Morris, ; Redondo & Morris, ).…”
Section: Discussionmentioning
confidence: 97%
“…Exogenous application of Aβ 1–42 impairs synaptic plasticity in vitro as well as in vivo , which underlies the process of memory formation (Ma et al ., ; Lei et al ., ). Deficits in associative learning have also been reported in the preclinical form of AD (Jiang et al ., ; Quenon et al ., ). STC model explains the formation of memories in an associative and time‐dependent manner (Frey & Morris, ; Redondo & Morris, ).…”
Section: Introductionmentioning
confidence: 97%
“…To compute this measure, the number of actual lag was calculated and normalized by the number of transition this participant performed in this trial. The normalization system used by Quenon et al (34) was employed since it yields a temporal contiguity measure that deals well with the minimal data available per condition/participant and is relatively insensitive to potential group-differences in overall recall level. The recall temporal contiguity measures were constructed only for the delayed recall trial, since these measure are known to change along the retrieval process in immediate recall and accordingly, different lag-CRP patterns are expected for each output position (i.e., for the 1st, 2nd, 3rd etc.…”
Section: Measures and Statistical Analysismentioning
confidence: 99%